Tracking of the hand "pressure point" on the grip of a recurve bow: a wearable solution - Bortoletto, R.; Mattiello, L.; Barzon, G.; Fazio, L.; Comotti, D.; Signorelli, M.; Motta, M. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to design and prototype a non-invasive wearable solution suitable for measuring speeds, accelerations and orientation of the hand-grip as well as the pressures between the hand and the grip of a recurve bow. Therefore, a device has been created that properly blends two technologies: an Inertial Measurement Unit (IMU) and a Force-Sensitive-Resistor (FSR) membrane. A preliminary evaluation of the device performance was conducted in collaboration with the Olympic athlete Mauro Nespoli. The obtained results demonstrate the potential of the proposed system, as well as highlight a number of interesting information from a biomechanical point of view, closely related to the shooting technique.